Age-associated changes in innate and adaptive immunity: role of the gut microbiota - Gao, Haoyu; Nepovimova, Eugenie; Adam, Vojtech; Heger, Zbynek; Valko, Marian; Wu, Qinghua; Kuca, Kamil (Frontiers in Immunology, 2024)
Aging is generally regarded as an irreversible process, and its intricate relationship with the immune system has garnered significant attention due to its profound implications for the health and well-being of the aging population. As people age, a multitude of alterations occur within the immune system, affecting both innate and adaptive immunity. In the realm of innate immunity, aging brings about changes in the number and function of various immune cells, including neutrophils, monocytes, and macrophages. Additionally, certain immune pathways, like the cGAS-STING, become activated. These alterations can potentially result in telomere damage, the disruption of cytokine signaling, and impaired recognition of pathogens. The adaptive immune system, too, undergoes a myriad of changes as age advances.These include shifts in the number, frequency, subtype, and function of T cells and B cells.Furthermore, the human gut microbiota undergoes dynamic changes as a part of the aging process. Notably, the interplay between immune changes and gut microbiota highlights the gut's role in modulating immune responses and maintaining immune homeostasis. The gut microbiota of centenarians exhibits characteristics akin to those found in young individuals, setting it apart from the microbiota observed in typical elderly individuals. This review delves into the current understanding of how aging impacts the immune system and suggests potential strategies for reversing aging through interventions in immune factors.